Інтер’єр Борисоглібського собору на світлинах та негативах з колекції «Фотонегативного фонду» Національного архітектурно-історичного заповідника «Чернігів стародавній» - Рига, Д.В. (Сіверщина в історії України, 2025)
На основі фотодокументів з «Фотонегативного фонду» Національного архітектурно-історичного заповідника «Чернігів стародавній» досліджується інтер’єр Борисоглібського собору – пам’ятки архітектури ХІІ ст. Методологія дослідження ґрунтується на принципах історизму, об’єктивності, аналізу, а також історико-порівняльному методі. Вперше зроблено спробу цілісного та комплексного вивчення фотоматеріалів з «Фотонегативного фонду», що фіксують інтер’єр собору ХІІ ст., та доцільність введення їх до наукового обігу. Впродовж всієї наукової діяльності Національного архітектурно-історичного заповідника «Чернігів стародавній» йшло поступове накопичення фотодокументів з історії пам’яток Заповідника. На сьогоднішній день одним з основних завдань закладу є введення до наукового обігу якомога більшої кількості наявних фотоматеріалів для всебічного дослідження історичних та унікальних архітектурних пам’яток стародавнього Чернігова, зокрема пам’ятки архітектури ХІІ ст. – Борисоглібського собору. Based on the study of photo documents from the «Photonegative Fund», investigate the issue of photo fixation of the interior of the historical architectural monument of the 12th century. Borysohlib Cathedral, in the fund of the National Architectural and Historical Reserve «Ancient Chernihiv». The research methodology is based on the principles of historicism, objectivity, analysis, as well as the historical-comparative method. Scientific novelty of the article: for the first time, an attempt has been made to conduct a holistic and comprehensive study of the availability of materials from the «Photonegative Fund» in the matter of preserving photos and negative materials from photofixation of the interior of the 12th century cathedral. The features and expediency of using and introducing photo materials from the history of the unique monument into scientific circulation have been identified and characterized. Throughout the entire scientific activity of the National Architectural and Historical Reserve «Ancient Chernihiv», there was a gradual accumulation of photo documents on the history of the reserve’s monuments, in particular, the Borysohlib Cathedral of the 12th century. Today, the main task, for example, architectural monuments of the 12th century. Borysohlib Cathedral, the introduction into scientific circulation of as much available photographic material as possible for a comprehensive study of the historical and unique architectural monuments of the ancient city of Chernihiv.